Golden Camellias: A Review - Tran Duc Manh; Nguyen Toan Thang; Hoang Thanh Son; Dang Van Thuyet; Phung Dinh Trung; Nguyen Van Tuan; Dao Trung Duc; Mai Thi Linh; Vu Tien Lam; Nguyen Huu Thinh; Nguyen Thi Thu Phuong; Tran Van Do (Archives of Current Research International, 2019)
Golden camellias or yellow camellias are species belonging to genus Camellia L., family Theaceae. Fifty two species were described in southern China and Vietnam. Active ingredients such as polysaccharides, polyphenols, saponins, and flavonoids are well known characteristics of golden camellias. Its leaves and flowers have been long traditionally used for health improvement. It was found to be able to inhibit transplanted cancer, lower blood pressure, lower blood lipid, lower cholesterol, and prevent atherosclerosis. Currently, it costs 320–700US per one kg of dry flowers. Such price attracts many local ethnic people to plant golden camellias for poverty reduction. This work reviews (1) species and natural distribution, (2) uses and healthcare values, (3) techniques for seedling production, planting and tending, and (4) opportunities and challenges for future development of golden camellias.